Dynamic Managerial Capabilities - Helfat, Constance E.; Martin, Jeffrey A. (Journal of Management, 2015)
The dynamic managerial capabilities literature has developed over the past decade to the point where a review and synthesis of relevant literature can move the scholarly conversation forward. The concept of dynamic managerial capabilities—the capabilities with which managers create, extend, and modify the ways in which firms make a living—helps to explain the relationship between the quality of managerial decisions, strategic change, and organizational performance. We clarify theoretical constructs and their relationships, review and synthesize empirical research on the role and impact of managerial capabilities directed toward strategic change, and suggest avenues for future research. Our review begins with an overview of theoretical conceptions of dynamic managerial capabilities. Then we organize the remainder of the review around the three core underpinnings of dynamic managerial capabilities: managerial cognition, managerial social capital, and managerial human capital. In our review, we examine evidence from studies of dynamic managerial capabilities and reinterpret evidence prior to the introduction of the dynamic managerial capabilities concept through that lens. Consistent with the dynamic managerial capabilities concept, empirical research shows that managers differ in their impact on strategic change and firm performance and that differences in managerial cognition, social capital, and human capital lead to different outcomes.